Dictionary of Indian philosophical concepts - Singh, Badri N. (Asha Prakashan, 1988)
Encyclopedic work.
Keywords: Philosophie hindoue - Dictionnaire; Philosophy, Indic -- Dictionaries; Indische Philosophie; Wörterbuch